Effects of leptin and ghrelin on neural cue-reactivity in alcohol addiction: Two streams merge to one river?. (February 2019) - Bach, Patrick; Bumb, Jan Malte; Schuster, Rilana; Vollstädt-Klein, Sabine; Reinhard, Iris; Rietschel, Marcella; Witt, Stephanie H.; Wiedemann, Klaus; Kiefer, Falk; Koopmann, Anne
Highlights: Higher leptin levels predicted lower alcohol cue-induced brain response in the striatum. Leptin levels were negatively associated with alcohol craving. Higher leptin levels predicted longer time to first heavy-relapse. Acylated ghrelin was positively associated with increased cue-induced activation in the insula and craving for alcohol. Total ghrelin showed no association to craving, cue-induced brain activation or relapse risk. Abstract: Leptin and ghrelin and a "cross-talk" between both hormones were implicated in the pathophysiology of alcohol dependence, both modulating alcohol craving and drug-seeking. To date, the neurobiological mechanisms underlying those effects are still little-known. We thus investigated the effect of leptin and ghrelin on alcohol cue-induced brain response, alcohol craving and relapse risk in alcohol-dependent subjects. Seventy abstinent alcohol dependent individuals underwent a functional magnetic resonance imaging (fMRI) alcohol cue-reactivity task and patients` alcohol craving was assessed. Plasma levels of leptin, total and acylated, active ghrelin were measured prior to the fMRI session. Additionally, relapse data was collected during a three-month follow-up. Associations between hormone levels, mesolimbic cue-reactivity, alcohol craving and relapse risk were tested. Leptin levels showed a significant negative association to alcohol cue-induced brain response in the striatum and alcohol craving. In addition, there was a significant effect of leptin on time to first heavy relapse in which higher leptin levels predicted longer times to first heavy relapse. Moreover, positive associations between acylated ghrelin and increased cue-reactivity in bilateral insulae as well as increased craving for alcohol during the fMRI task were revealed. Leptin and acylated ghrelin show opposing effects on mesolimbic cue-reactivity and alcohol craving. We suspect that the reduced striatal cue-reactivity might be the neurobiological correlate of leptin's effect on relapse-risk. The reported results further support the relevance of appetite regulating hormones in the pathophysiology of addiction and their potential role as future treatment targets.